IMPROVING THE LEARNING OUTCOMES OF CLASS IV STUDENTS IN INDONESIAN LESSON ABOUT FICTION STORIES USING AUDIO VISUAL MEDIA - Ayu Nur Fitri; Enung Nurhayati (IKIP Siliwangi, 2022)
This study was conducted with the aim of knowing (1) student learning outcomes before using audio visual media in B.Indonesia subjects for grade IV students (2) student learning outcomes after using audio visual media in B.Indonesia subjects for grade IV students. This research is a quantitative descriptive study. The subjects of this study are the fourth grade students of SDN 3 Cimerang, with a total of twenty students. Data collection techniques used in this study were observation and tests. The results of the study concluded that the learning outcomes of B.Indonesia fourth grade students increased. Learning outcomes before using audio-visual media obtained learning outcomes with an average class of 69.25 the number of students who complete is 12 students or 60% and the number of students who have not completed is eight students or 40%. Whereas after using audio-visual media the learning outcomes have increased again, with an average grade of 85.5 the number of students completing is 18 people or 90% and the number of students who have not completed is two people or 10%. Based on the findings and discussion it can be concluded that learning B.Indonesia by using audio visual media can improve the understanding and learning outcomes of fourth grade students.